Detection of Mycobacterium avium subspecies paratuberculosis of dairy cows in Bogor - Nugroho, Widagdo Sri; Sudarwanto, M.; Lukman, D.W; Setiyaningsih, E.; Usleber, E. (Indonesian Animal Sciences Society, 2009)
Johneâs disease (JD) or partuberculosis is a chronic granulomatous enteritis in ruminants caused by infection of Mycobacterium avium paratuberculosis subspecies (MAP). The disease has been detected serologically in Indonesia. Itâs potential to spread to other herds and could create great economic losses. The objectives of current study were to detect MAP in milk and faeces of dairy cows as well as to evaluate the association between farm management factors and presence of the bacteria in dairy cows in Bogor. The sample size was calculated using the formula to detect disease with the prevalence assumed to be 5% using 95% significant level. Milk and faeces samples were taken from 62 dairy cows which were suspected as suffering from MAP infection. Detection of MAP was done by isolation in Herroldâ egg yolk medium with mycobactin J (HEYMj), acid-fast bacilli Ziehl-Neelsen staining, PCR IS900 and F57. Biochemical test to confirm M. tuberculosis presence was also conducted. Fifteen isolates of Mycobacterium sp. were found from the faeces samples but not from the corresponding milk samples. However, conventional PCR conducted on the isolate as well as the milk samples, gave negative results. Biochemical test proved that all Mycobacterium sp. isolates were not M. tuberculosis. This study indicated the prevalence of MAP in Bogor was less than 5%. These findings should be continued by observational study to achieve the comprehensive information at the cattle and herd level. Bovine Tuberculosis monitoring should be done also to protect dairy herd and food safety for the community. Key words: Johneâs disease, Mycobacterium avium subspecies paratuberculosis, Milk, Faeces